Dimensions in the Adoption of Philippine Tax E-Payment Channels in Paying Income Taxes Among Individual Taxpayers - Lord Eddie I. Aguilar (Yayasan Ilomata, 2023)
Time has entered the digitized era where electronic systems have penetrated transactions, including taxation, simplifying processes among taxpayers for better revenue collection. With the aim of helping tax authorities in administering revenue collection, the study determines the factors influencing the adoption of the Philippines tax e-payment channels in paying income taxes among individual taxpayers and develop a research framework that illustrates the relevance and structure of the extracted factors. Using the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) as a guide model, the study applies the quantitative research method as the research design. The assumption of the adoption of e-payment channels in paying income taxes among individual taxpayers is multifaceted that is based on the perception of the relative technology system. An Exploratory Factor Analysis (EFA) was employed to analyze a dataset of 110 respondents using random sampling collected through modified questionnaires. The study revealed that perceived usefulness, perceived benefit, perceived trust, social influence, facilitating conditions, and perceived cost influence the adoption of the BIR e-payment channels in paying income taxes among individual taxpayers in Davao City.